PENGARUH RELATED PARTY TRANSACTIONS TERHADAP PENGGUNAAN MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - William Teguh; Rizky Eriandani (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2021)
The company's profit can be one of the factors that can determine an investor's decision to make an investment. The company's large and growing profits will surely be attractive to investors. However, the profit reported by the company does not necessarily guarantee that the reported information is the actual condition of the company. Companies can do earnings management resulting from gaps in information between company management and external parties. One of the activities that can be used as an earnings management tool is RPT. This study aims to determine whether RPT is positively related to real earnings management or accrual earnings management on manufacturing companies in Indonesia during the period between 2017-2019 that have been listed on the Indonesia Stock Exchange. The results showed that RPT has no significant effect on real earnings management or accrual earnings management. These results indicate that RPT is used not for earnings management purposes but as an efficient transaction. There are also other factors that influence earnings management such as audit quality and the number of directors.